Stilbestrol and Synovex implants (and reimplants) for steers on a fattening ration. - Koch, B.A.; Smith, E.F.; Cox, R.F.; Richardson, D.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
The steers used in this fattening trial were part of a larger group used in a wintering trial reported on page 46 of Kansas Circular 358. At the beginning of the fattening period the ration was gradually changed from a high roughage, wintering type, to a high energy, fattening type. Also at that time five of the steers in the stilbestrol lot were reimplanted with 24 mgs. of diethylstilbestrol and five steers in the synovex lot were reimplanted with synovex. Individual calves remained in the same experimental group as during the wintering study but the groups were moved from the outdoor lots to concrete lots in which shelter was available.
Keywords: Beef; Stilbestrol; Synovex; Ration